An historical political economy analysis of high-emissions low-employment development in South Africa - Van, Doesburgh Nicholas (African Climate and Development Initiative, 2023)
South Africa is grappling with persistently high levels of poverty, inequality and unemployment, while at the same time being one of the top twenty greenhouse gas emitters in the world. While calls have been made for South Africa to embark on a just transition to a lowcarbon society, a better understanding is needed of the factors that have led to the country's current unsustainability. Drawing on the concept of the minerals-energy complex, this thesis presents an historical political economy analysis of South Africa's industrialisation process in order to (1) identify the key factors that have contributed to the country's high emissions and low employment; and (2) to determine the role of industrial policy in shaping this unsustainable development pathway. The analysis shows that the capital- and energy-intensive characteristics of South Africa's industrial structure have contributed to the country's high unemployment and high emissions. While industrial policy has been instrumental in shaping this industrial structure, its role in the post-apartheid era has been complicated by the existence of a ‘hidden' industrial policy in conflict with official objectives as well as implementation challenges which together have constrained the effectiveness of policies aimed at inclusive decarbonisation. From these results, it is argued that the adoption of an integrated green industrial policy has an important role to play in enabling South Africa to embark on a just transition to an inclusive low-carbon society.